(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Thepresent study explores the participation of the resident of NCR in properdisposal of waste. Researcher has attempted to collect primary data on persondisposing waste, methods of disposing waste, treatment of reusable waste,practice of carrying shopping bag and, knowledge of colour of dustbins. Thisstudy will provide policy makers and communication campaign designer usefulinformation regarding the waste disposal habit of the respondent.